Optimization of Extraction of Inulin from Taraxacum kok-saghyz Rodin by Response Surface Methodology and Its MALDI-TOF MS Analysis - Jiangyan CHEN; Weitao WANG; Yiyang DONG; Jichuan ZHANG; Kongxin HU; Qiang MA (Shipin gongye ke-ji, 2022)
Using Taraxacum kok-saghyz Rodin root as raw material, the effects of ultrasonic power, extraction time, ultrasonic temperature and liquid-solid ratio on the extraction rate of inulin from Taraxacum kok-saghyz Rodin root were studied based on single factor experiment and response surface experiment. The optimum extraction conditions of inulin from Taraxacum kok-saghyz Rodin root were as follows: Ultrasonic power 230 W, ultrasonic time 34 min, ultrasonic temperature 61 ℃, liquid-solid ratio 30:1 (mL:g), and the extraction rate of inulin was 20.14%±0.19%. The calcium hydroxide-phosphoric acid method, trichloroacetic acid method and Sevage method were used for protein purification, and the results showed that the calcium hydroxide-phosphoric acid method had the best effect, with a protein clearance rate of 90.78% and an inulin loss rate of 26.44%. Inulin with a purity of 80.8% was obtained after protein purification, decolorization, alcohol precipitation and vacuum freeze drying, was a white solid powder. The obtained inulin was characterized and analyzed by MALDI-TOF MS, which determined that the molecular weight of the monomer was 162, the molecular weight of the end group was 179, and the degree of polymerization can be detected in the range of 2 to 30. This study provides a theoretical basis for the comprehensive utilization of Taraxacum kok-saghyz Rodin.